Ordered phase transformation and Cu doping effects in room-temperature ferromagnetic Sr3YCo4O10.5+δ - Ren, Lingqi; Zhang, Xiaodong; Du, Xiaoli; Wang, Jianlu; Yu, Lan (Frontiers in Chemistry, 2022)
Sr3YCo4O10.5+δ (314-SYCO), with an unusual ordered structure and a high Curie temperature (Tc  335 K), is attracting increasing attention. Herein, to improve the electrical performance of 314-SYCO, Cu-doped Sr3YCo4−xCuxO10.5+δ (x = 0–0.8) ceramics were prepared using a solid-state reaction method. Systematic research was conducted on both the ordered phase transformation and the effects of Cu doping on the microstructure, electrical transport characteristics, and magnetic properties. For x = 0–0.4, the (103) and (215) planes were observed and combined with Rietveld refinement results for the X-ray diffraction data, confirming the formation of ordered tetragonal Sr3YCo4−xCuxO10.5+δ. This phase was formed with a mass gain of ~0.8% and heat released at ~1042°C. With increasing Cu content, the concentration of hole carriers also increased, leading to a substantial reduction in electrical resistivity. The electrical resistivity decreased by 92–99% at 300 K. The polycrystalline materials have semiconducting behaviour with a three-dimensional Mott variable-range hopping mechanism. For the magnetic properties, a Hopkinson peak was observed at 319 K, and the Tc was approximately 321 K for x = 0. The magnetisation and Tc decreased with increasing Cu content, and a G-type antiferromagnetic-to-ferromagnetic phase transition occurred due to the spin state change for some Co3+ ions from high/intermediate spin to low/intermediate spin. These results lay the groundwork for refinement of the sintering procedure and doping parameters to enhance the performance of 314-SYCO in the context of current applications such as microwave absorbers and solid oxide fuel cell cathodes.